2023
DOI: 10.3389/fonc.2023.1085188
|View full text |Cite
|
Sign up to set email alerts
|

A pyroptosis-related gene signature for prognosis prediction in hepatocellular carcinoma

Abstract: IntroductionHepatocellular carcinoma (HCC) is one of the most invasive cancers with a low 5-year survival rate. Pyroptosis, a specialized form of cell death, has shown its association with cancer progression. However, its role in the prognosis of HCC has not been fully understood.MethodsIn our study, clinical information and mRNA expression for 1076 patients with HCC were obtained from the five public cohorts. Pyroptotic clusters were generated by unsupervised clustering based on 40 pyroptosis-related genes (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…A list of markers associated with pyroptosis in HCC was published, which includes BAK, BAX, caspase 1, 3 and 5, gasdermin A and E, high-mobility group box 1, interleukin 18, 1A and 1B, p53, tumor protein 63, among others [135,136]. Of importance, among these genes, p53 is of interest, given its involvement in metformin-and sorafenib-related mechanisms of cell death.…”
Section: Cell Death Mechanism Activated By the Combination Of Metform...mentioning
confidence: 99%
See 1 more Smart Citation
“…A list of markers associated with pyroptosis in HCC was published, which includes BAK, BAX, caspase 1, 3 and 5, gasdermin A and E, high-mobility group box 1, interleukin 18, 1A and 1B, p53, tumor protein 63, among others [135,136]. Of importance, among these genes, p53 is of interest, given its involvement in metformin-and sorafenib-related mechanisms of cell death.…”
Section: Cell Death Mechanism Activated By the Combination Of Metform...mentioning
confidence: 99%
“…Of importance, among these genes, p53 is of interest, given its involvement in metformin-and sorafenib-related mechanisms of cell death. It was shown that the analysis of the clusters of pyroptosis is useful to predict prognosis in patients with HCC [135].…”
Section: Cell Death Mechanism Activated By the Combination Of Metform...mentioning
confidence: 99%